Radical approaches to political science: roads less traveled - Eisfeld, Rainer (Budrich, 2012)
"In this comprehensive volume, Rainer Eisfeld draws judicious lessons from his long-time involvement in international debated about what political science does - and what it should be able to achieve. Highlighting problems too rarely confronted by "mainstream" political scientists, the book's innovative chapters explore salient contemporary issues in a manner apt to stir up conventional thinking: the non-relevance of political science research for improving the human condition; today's deficient political pluralism; the susceptibility of political science to authoritarian temptations; the fatal extent of American 'Gun-mindedness'; the discipline's development in post-communist countries, overshadowed by the emergence of hybrid regimes. Tying together a dozen original contributions with a determined emphasis on participatory politics, Eisfeld demonstrates how 'radical' approaches promote the sort of political science that does not shy away from incorporating historical dynamics, societal conflicts, and embedded power relations."--Page 4 of cover
Keywords: Politische Wissenschaft